2010
DOI: 10.4081/dr.2010.e1
|View full text |Cite
|
Sign up to set email alerts
|

Keratoacanthoma centrifugum marginatum: unresponsive to oral retinoid and successfully treated with wide local excision.

Abstract: We describe a case of a 65-year-old male presenting with a large plaque with a rolled-out interrupted margin, atrophic center, and island of normal skin over the left arm. It grew peripherally with central healing, and there was a history of recurrence after inadequate excision. Investigations ruled out other clinical mimickers; namely, squamous cell carcinoma, lupus vulgaris, botryomycosis, and blastomycosis-like pyoderma. Histopathological sections showed irregularly shaped craters filled with keratin and ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Our patient had a good and prompt response to acitretin. However, Mangas et al 13 and Das et al 14 reported failure of oral retinoids in their patients. Patients successfully treated with oral retinoids are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 95%
“…Our patient had a good and prompt response to acitretin. However, Mangas et al 13 and Das et al 14 reported failure of oral retinoids in their patients. Patients successfully treated with oral retinoids are summarized in Table 2.…”
Section: Discussionmentioning
confidence: 95%
“…Some cases treated with oral retinoids (Acitretin, Etretinate or Isotretinoin in doses between 0.5 and 1 mg/kg/day) with a good response (Georgescu et al, ; Mehrtens, de la Hera, & Shankar, ) have been reported. One case without response oral retinoids has been successfully treated with wide local excision (Das et al, ). Mohs surgery, conventional surgery, PDT, or radiotherapy has also been used (Lindsay, Kharofa, Junck, Olasz, & Frank Wilson, ; Sung et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…It is hypothesized that this typical appearance may arise as a result of sequential involvement of multiple adjacent hair follicles in a centrifugal fashion. [9]…”
Section: Discussionmentioning
confidence: 99%